Influence of Socio-Economic Characteristic on Travel Behaviour in Malang City - Taufikkurrahman Taufikkurrahman; Pratikso Pratikso; Kartono Wibowo (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Rapid urbanization and economic growth in Malang City have significantly influenced urban mobility patterns, increasing dependence on private vehicles and reshaping commuting behavior. Understanding the socio-economic determinants of travel behavior is therefore essential for sustainable transport planning in secondary cities in Indonesia. Objective: This study analyzes the relationship between socio-economic factors (such as age, income, education, occupation, gender, household size, and vehicle ownership) and daily travel behavior in Malang City, including trip frequency, trip purpose, and transport mode choice. Methods: A quantitative cross-sectional design was applied using a structured questionnaire distributed to 200 households selected through non-probability sampling. The data were analyzed using descriptive statistics and stepwise multiple linear regression to examine the effects of socio-economic variables on different dimensions of travel behavior. Results: Education was the only significant predictor of trip frequency (B = 0.081, p < 0.001; R² = 0.140). For trip purpose, the model demonstrated strong explanatory power (R² = 0.610, F = 50.300, p < 0.001), with occupation (β = 0.706, p < 0.001), education (β = 0.132, p = 0.006), and income (β = −0.107, p = 0.021) identified as significant determinants. However, none of the socio-economic variables significantly influenced transport mode choice (R² = 0.010, p = 0.931), indicating that infrastructure conditions and transport service availability may play a more dominant role in determining mode selection. Conclusion: Socio-economic factors influence travel behavior differently across various dimensions. While these factors significantly affect trip frequency and trip purpose, they do not determine transport mode choice.